Effect of the boiled cumin seeds extract in the glucose, some hormones concentration and aortic tissue in New Zealand white male rabbits fattened experimentally - Muntaha M. Al-Kattan; Iman M. S. Jallod (Tikrit Journal of Pure Science)
The present study was performed in Department of Biology/College of Science/University of Mosul to determine the effect of fattening New Zealand Albino male rabbits experimentally and use boiled cumin seeds extract in the glucose ,some hormones concentration and aortic tissue. It used 40 male from New Zealand albino rabbits and ages ranged from 10.8 months and weights ranging from 1400-1250gm,, divided into two groups of 20 rabbit / group and putted in separate cages. Fed  the first group to standard diet, while the second group fed special diet rich in fat for the purpose of fattening for a period of 12 weeks after a period all rabbits were weighted, and divided into four groups of 10 rabbit / group,  are control group,  Cumin group, fattening group and fattening with cumin: , all these groups underwent   standard condition of water and diet,, cumin group and group and fattening with cumin group dosing with2000 mg / kg body weight boiled cumin seeds extract for 8 weeks where a daily dosage.